(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we introduce the concept of slightly compressible-injective modules, following this, a right R-module N is called an M-slightly compressible-injective module, if every R-homomorphism from a non-zero M-slightly compressible submodule of M to N can be extended to M. We give some characterizations and properties of slightly compressible-injective modules.